2020
DOI: 10.1101/2020.01.17.911107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphorylation-Dependent Assembly of a 14-3-3 Mediated Signaling Complex During Red Blood Cell Invasion byPlasmodium falciparumMerozoites

Abstract: 232 words; Text: 5494 words 23 24 25 Abstract 29Red blood cell (RBC) invasion by Plasmodium merozoites requires multiple steps that are regulated by 30 signaling pathways. Exposure of P. falciparum merozoites to the physiological signal of low K + , as 31 found in blood plasma, leads to a rise in cytosolic Ca 2+ , which mediates microneme secretion, motility, 32 and invasion. We have used global phosphoproteomic analysis of merozoites to identify signaling 33 pathways that are activated during invasion. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…2 ) [50] . Post-translational modifications of CDPKs are responsible for modulating the activity, localization and interaction of CDPKs with their cognate substrates [84] , [79] , [2] . Myristoylation of a conserved glycine residue (Gly 2 ) at the N-terminus of PfCDPK1 is critical for its membrane localization in schizonts and merozoites [84] .…”
Section: Domain Organization and Calcium Mediated Activation Of Cdpksmentioning
confidence: 99%
See 3 more Smart Citations
“…2 ) [50] . Post-translational modifications of CDPKs are responsible for modulating the activity, localization and interaction of CDPKs with their cognate substrates [84] , [79] , [2] . Myristoylation of a conserved glycine residue (Gly 2 ) at the N-terminus of PfCDPK1 is critical for its membrane localization in schizonts and merozoites [84] .…”
Section: Domain Organization and Calcium Mediated Activation Of Cdpksmentioning
confidence: 99%
“…It has been suggested that phosphorylation of RhopH3 is mediated by CDPK1 [33] . A recent elegant study by More et al, demonstrates formation of a multimeric complex in merozoites involving phosphorylated CDPK1, regulatory subunit of PKA (PKAr) and Pf14-3-3I that plays a critical role in the invasion process and microneme discharge [79] . These studies suggest an essential role for CDPK1 in asexual proliferation of the parasite and as such, corroborates well with the inability to delete CDPK1 in the WT parasite background.…”
Section: Cdpks and Asexual Intra-erythrocytic Development Of Malaria Parasitementioning
confidence: 99%
See 2 more Smart Citations
“…Protein kinases possess a strong potential as antimalarial targets given their crucial role for parasite survival ( 5 ). A substantial body of work highlights the role of this enzyme class in the regulation of host cell invasion ( 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ). For instance, the physiological role of protein kinase A, casein kinase 2 (CK2) as well as glycogen synthase kinase 3 (GSK3) during the host cell invasion has been demonstrated ( 6 , 7 , 8 , 9 , 10 , 16 , 17 , 18 , 19 ).…”
mentioning
confidence: 99%